2020
DOI: 10.3389/fspor.2020.587789
|View full text |Cite
|
Sign up to set email alerts
|

Device-Based Measures of Sedentary Time and Physical Activity Are Associated With Physical Fitness and Body Fat Content

Abstract: Introduction/Purpose: Physical activity and sedentary time may associate with physical fitness and body composition. Yet, there exists some observational studies that have investigated the associations of device-based measures of sedentary time and physical activity (PA) with cardiorespiratory fitness (CRF) and body composition but associations with muscular fitness (MF) are less studied.Methods: Objective sedentary time and physical activity was measured by a hip worn accelerometer from 415 young adult men (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…In previous studies, accelerometry-measured absolute total physical activity level has been higher in men than women, decreased by BMI, and increased by aerobic fitness level (Dyrstad et al, 2016;Kujala et al, 2017;Tucker et al, 2011;Vaara et al, 2020). Such estimations of absolute physical activity can lead to underestimated physical activity in those with a lower aerobic fitness level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, accelerometry-measured absolute total physical activity level has been higher in men than women, decreased by BMI, and increased by aerobic fitness level (Dyrstad et al, 2016;Kujala et al, 2017;Tucker et al, 2011;Vaara et al, 2020). Such estimations of absolute physical activity can lead to underestimated physical activity in those with a lower aerobic fitness level.…”
Section: Discussionmentioning
confidence: 96%
“…However, accelerometer-measured physical activity intensity lacks consideration for an individual's fitness level. People with a high aerobic fitness level have more moderate and vigorous physical activity and are more likely to meet the current physical activity guidelines defined as 150 min/week of moderate to vigorous physical activity when estimated with accelerometry (Dyrstad et al, 2016;Vaara et al, 2020). When the activity volume is considered relative to maximal fitness, people with high and low aerobic fitness levels have a more similar activity profile (Kujala et al, 2017).…”
mentioning
confidence: 99%
“…They have both relevance and significance as characteristics of trainee's ability to deal with and recover from the physical component of the stress. Furthermore, exhaustive physical activity, which in this study occurred at the extended training days of D20* and D42*, is known to effect affective state ( Henning et al 2011 ; Vaara et al, 2020 ; Lieberman et al, 2016 ). Levels of Cl, an electrolyte found in blood, were significantly higher in non-grads at both D1 and at D52 compared to that in grads.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have identified strain or individual differences in reactivity to stress, whether physical or emotional ( Solberg et al, 2006 ; Mann et al 2014 ). Since stress affects both physiological and affective processes ( Henning et al 2011 ; Vaara et al, 2020 ; Lieberman et al, 2016 ), the ideal measures of stress reactivity would contain some of these factors. The most well-known physiological stress response is the activation of the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Introductionmentioning
confidence: 99%
“…To strengthen the evidence based on sedentary behavior as an adult health risk, a large number of longitudinal studies have been conducted to investigate the association between sedentary behavior and health outcomes among adults, but the findings have been mixed [ 9 , 10 , 11 , 12 , 13 ]. Some studies have reported that sedentary behavior is associated with health outcomes.…”
Section: Introductionmentioning
confidence: 99%